Radical cation Diels–Alder reactions of arylidene cycloalkanes - Nakayama, Kaii; Kamiya, Hidehiro; Okada, Yohei (Beilstein Journal of Organic Chemistry, 2022)
TiO2 photoelectrochemical and electrochemical radical cation Diels–Alder reactions of arylidene cycloalkanes are described, leading to the construction of spiro ring systems. Although the mechanism remains an open question, arylidene cyclobutanes are found to be much more effective in the reaction than other cycloalkanes. Since the reaction is completed with a substoichiometric amount of electricity, a radical cation chain pathway is likely to be involved.
Keywords: arylidene cycloalkane; Diels–Alder reaction; radical cation; single-electron transfer; spiro ring system